ECOLOGICAL AWARENESS OF THE MANAGERS IN TOURISM ACCOMMODATION FACILITIES ABOUT THE ANTHROPOGENIC CAUSE OF THE CLIMATE CHANGE AND THE CAUSAL INFLUENCE OF TOURISM ON CLIMATE CHANGE - Racz, Aleksandar (Horizons - International Scientific Journal, 2020)
Taking into account all other environmental problems, climate change has become the biggest challenge and threat to the survival of human civilization, withmanyconsequencesand a expansiveand wide influence on virtuallyeveryaspectof human life, andundoubtedly on tourism as anactivity. The main objective of the research was to examine and analyze the ecological awareness of the managers in tourism accommodation facilities about the anthropogenic cause of the climate change and the negative causal influence of tourism on global warming and climate change. The data were collected during 2019 by a survey method conducted between managers in categorized accommodation facilities in Croatia. Kolmogorov-Smirnov's test analyzed the distribution of continuous numerical values and according to the obtained data corresponding non-parametric tests were applied. Categorical and nominal values were shown using corresponding frequencies and shares. Continuous values were shown using medians and interquartile ranges.The results have shown that managers had a developed the certain lever of the ecological awareness of the importance of global climate change issue, but did not sufficiently recognize the causal link between tourism, atmospheric pollution and global warming with the effects of climate change.